Air Quality: Source Apportionment Approaches and Techniques - Khobragade, Pallavi Pradeep; Ahirwar, Ajay Vikram (Air Quality: Source Apportionment Approaches and Techniques, 2021)
Clean air is seen as a fundamental prerequisite for human health and happiness. However, air pollution continues to be a major health concern around the world. Polluted air is inconvenient and can pose a major health risk in cities when it is present in high amounts. The first approach to enhance air quality is to recognize that a healthy atmosphere is just as important as the development of new technology that raise people's living standards. This book aims to inform the reader on the broad spectrum of air quality sources, air quality control, chemical characterization, while also directing his attention to specific issues that arise in practical work of source identification using receptor models with a practical example of model validation. The book also discusses the objectives of source apportionment, physical and chemical characterization of aerosols, different air quality models including dispersion and receptor models and back-trajectory analysis using National Oceanic and Atmospheric Administration (NOAA) Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model. Dealing with the air quality issue and contributing sources is necessary as a complement to the national discourse and challenges of global warming and climate change.